PSMD14-mediated deubiquitination of CARM1 facilitates the proliferation and metastasis of hepatocellular carcinoma by inducing the transcriptional activation of FERMT1 - Jing Lu; Huita Wu; Ping Zhan; Yuyan Lu; Qinliang Fang; Changhong Luo; Fuqiang Wang; Jing Wen; Chengrong Xie; Zhenyu Yin (Cell Death and Disease)
Abstract Hepatocellular carcinoma (HCC) is a highly potent malignancy. The enzyme coactivator-associated arginine methyltransferase 1 (CARM1) is highly expressed in different types of cancer. However, the precise levels of expression, clinical significance, biological functions, and molecular mechanisms of CARM1 in HCC, particularly related to the downstream genes regulated by CARM1 through histone arginine methylation, remain unclear. In this study, we presented findings from the TCGA database and clinical samples, which collectively demonstrated the overexpression of CARM1 in HCC. Additionally, we found that the upregulation of CARM1 was mediated by PSMD14-induced deubiquitination. CARM1 promoted the proliferation and metastasis of HCC cells in vitro and in vivo. Mechanistic investigations further revealed that FERMT1 is a downstream gene of CARM1, and CARM1 activates the transcription of FERMT1 through the dimethylation of arginine 17 on histone 3 (H3R17me2). Additionally, administering SGC2085, a CARM1 inhibitor, effectively suppressed the malignant behaviors of HCC cells. To summarize, our findings provided strong evidence that CARM1 can serve as a key oncoprotein; thus, it holds promise as a therapeutic target for HCC.